PERBANDINGAN ANALISIS FUNDAMENTAL TERHADAP HARGA SAHAM PERUSAHAAN BATUBARA DAN PERKEBUNAN DI BURSA EFEK INDONESIA - Eddy Mulyadi Soepardi (MAGMA : JURNAL MAGISTER MANAJEMEN, 2007)
This study aimed to analyze the influence of fundamental analysis on stock price Coal and Oil companies listed in Indonesia Stock Exchange 2011-2015. Samples in this research that the company Coal as many as 13 companies and plantation companies as many as 10 companies. Sampling in this study using purposive sampling. Data were analyzed using panel data analysis. The results showed that: First, partially Fundamental Analysis with significant influence on stock price of coal company is Cash Ratio (CR) and Return on Equity (ROE). Second, partially Fundamental Analysis with significant influence on stock price of companies Plantation is Cash Ratio (CR), Return on Equity (ROE), and Total Assets Turn Over (TATO). Third, the simultaneous analysis of Fundamental measured by using the Cash Ratio (CR), Return on Equity (ROE), Debt to Equity Ratio (DER), Earning Per Share (EPS), and Total Assets Turnover (TATO) have significantly influenced companies coal and OilKeywords: Fundamental Analysis and Stock Price